Investigating the Upbringing in Education with the Case of M.M. Speransky's Educational System - Rumyantseva, Nataliya M. (2020)
M.M. Speransky is a famous Russian public and political figure. However, his activities were not limited to political issues. His pedagogical activity is studied poorly. The basic principles of the younger generation upbringing were laid during the seminar period, which coincided in time with the pedagogical activity by M. Speransky. The success of Speransky’s pedagogical system is evidenced by the fact that he was invited as an educator to the royal family. The basic principles of Speransky's pedagogy were the following ones: the authority of a teacher, but the lack of authoritarianism, the interaction with a student in the search for the right educational solutions, the attachment to the students and responsibility for them.